Stability of phenolics compounds in freeze dried berry products with typically long shelf life - Biswas, Dipankar (My University, 2022)
Berries are a potentially rich source of polyphenols, particularly anthocyanins, which may play an important role in the increased risk of chronic diseases. Anthocyanins, which are found primarily in fruits and vegetables, are gaining popularity due to their potential antioxidant activity, but they are highly susceptible to degradation during processing and storage. One of the most important quality characteristics of food products is the stability of anthocyanin content during processing and storage. Freeze-drying is a preservation method where water is removed by sublimation from the frozen material. Typically, the process is used with high-value raw materials, such as berries, which can be used as ingredients in mueslis and granolas. Aim of this study was to evaluate the effect of storage on anthocyanin and flavonol compositions and contents and total antioxidant activity in different freeze-dried berries maintained at accelerated storage (40 °C for 1-6 months). Samples were muesli packages including freeze-dried strawberry, black currant or blueberry material prepared in Estonia. Identifications and quantifications of the phenolic compounds were carried out using HPLCDAD and HPLC-MS instruments. Total anthocyanin found in Blackcurrant (at Day zero) 288.9 mg/100g dry matter, In Blueberry 836 mg/100g and in Strawberry 126.5 mg/100g. After two month of storage (56 days), all berries resulted in significant losses in anthocyanins with as much as 60% in strawberry, 60% in blueberry and 46% in blackcurrant compared to Day 0. In addition, after 56 days to 120 days’ anthocyanin losses were less 21% in strawberry, 59% in Blueberry and 29% in Blackcurrant compared to Day 0 with 100%. In contrast, variety of flavonols detected and quantified with HPLC from the samples remained unchanged during the first months of storage.
Keywords: Blackcurrant, Strawberry, Blueberry, Anthocyanin, Identification, Degradation, Storage, HPLC-DAD